Enhancing The Performance of LSB Steganography with RSA and Huffman - Muhammad Rifqy Abdul Gofur Al Fatah; Denar Regata Akbi; Bashor Fauzan Muthohirin (P3M Politeknik Negeri Banjarmasin, 2026)
The growing sophistication of digital threats has exposed major vulnerabilities in traditional data protec-tion methods, particularly those that rely only on cryptography or steganography. These single-layer tech-niques often fail to ensure both data confidentiality and concealment, which makes information more vulnera-ble to detection and attack. This study addresses the limited effectiveness of existing security mechanisms in balancing secrecy, efficiency, and image quality. Therefore, this study aims to develop a multi-layer steganog-raphy system that integrates Huffman-based data compression, enhanced RSA encryption, and optimized Least Significant Bit (LSB) embedding to improve data protection and performance. The proposed model was imple-mented in Python with a graphical user interface to improve usability. The experimental results show high im-perceptibility, with a Peak Signal-to-Noise Ratio (PSNR) of 48.32 dB and a Structural Similarity Index (SSIM) of 0.9987, indicating minimal visual distortion. Security testing confirmed resistance to steganalysis and brute-force attacks, while performance evaluation showed stable processing efficiency. These findings indicate that the proposed system offers a secure, efficient, and practical framework for digital information hiding in modern communication environments.